Synergists for agave weevil Scyphophorus acupunctatus (Coleoptera: Dryophthoridae) trapping on Agave angustifolia (Asparagaceae), in Guerrero, Mexico - Cuevas-López, Daniel; Hernández-Castro, Elías; Romero-Rosales, Teolincacihuatl; Segura-Pacheco, Héctor Ramón; Figueroa-Castro, Pedro; Gonzalez-Hernádez, Héctor (Revista Colombiana de Entomología, 2023)
Scyphophorus acupunctatus (Coleoptera: Dryophthoridae) attacks several species of native agaves and it is the most important insect pest of cultivated agaves in Mexico. The management of this insect is difficult due to its feeding habits on agave stems and leaves. Recently, a trapping system based on a synthetic aggregation pheromone and food bait has been developed to monitor and capture adult S. acupunctatus. However, it is important to know some alternatives that can synergize the response of S. acupunctatus to the synthetic pheromone. In this study, two consecutive field trials were carried out where diverse synergists were evaluated in traps placed in a plantation of Agave angustifolia (Asparagaceae), in Quetzalapa, Guerrero, Mexico. The synergists evaluated were the following: plant tissue of A. angustifolia, ripe fruits of pineapple (Ananas comosus), and banana (Musa paradisiaca) as well a synthetic synergist (Sinergium®). In all the experiments, a completely randomized design was used, with four repetitions for each treatment. The synergists evaluated had no effect on the captures of S. acupunctatus. The capture averages of S. acupunctatus/trap/day in the experiments did not differ, which is why it is suggested that in plantations with initial or low infestations (up to 5 weevils) it is not required to add synergists, while at high densities (more than 5 weevils) it is advisable to use a plant or synthetic synergist (Sinergium®) to make synergy with the synthetic pheromone. In addition, more female (192) than male (137) were captured in traps, which may impact future pest density populations of the weevil, plant health, and agave producer economics.